Georgia : Sixth Review Under the Stand-By Arrangement and Requests for Modification of Performance Criteria, Waiver of Nonobservance of Performance Criterion, Waiver of Applicability of Performance Criterion, and Rephasing of Purchase; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report, 2010)
The economic recovery has gained strength in Georgia. The corrective policy actions provide adequate assurances that the program objectives are on track. The success in mobilizing additional budgetary support and diversifying their financing sources is commended. Postponing implementation of a referendum requirement on tax increases, until the fiscal deficit has been returned to prudent levels, enhances policy flexibility. The recent tightening of monetary policy is warranted and should continue. The exit strategy has been reinforced by improvements in confidence accompanying the rebound in activity.